Innovations From The Use Of Computational Solutions: An Overview Focused In The Mining Industry - Luiz Gustavo Franco Amaral (Associacao Brasileira de Metalurgia, Materiais e Mineracao, 2019)
The recent tragedies that occurred in Brazilian territory had a greater impact than that presented in the major newspapers and led an entire industry to question the technology and techniques that were previously practiced in the mining industry. With this, there is the prospect of new projects and innovations in the most varied branches of engineering. This publication presents computational technologies to support the decision making of engineering projects aimed at the mining sector and explores the benefits obtained from the use of current technologies in the mining sector. Recent works are referenced in order to propagate not only the methodology employed in these researches, but also to provide the reader with an overview of the industry and companies that invest in technology to support their decision making in the most diverse projects gains on products and processes obtained through this practice.